Psychotic-like experiences and associated socio-demographic factors among pregnant women in each trimester in China - Lu, Dali; Qiu, Shuangyan; Xian, Danxia; Zhang, Jingyu; Zhang, Yan; Liu, Xiaocheng; Yang, Weikang; Liu, Xiaoqun (Frontiers in Psychiatry, 2022)
Objective Psychotic-like experiences (PLEs) are quite common in the general populations without a clinical diagnosis, but pregnant women have been neglected in earlier literature. This study aimed to investigate the prevalence and correlates of PLEs among pregnant women without previous psychiatric history in each trimester. Method A total of 950 pregnant women participated in a cross-sectional survey, with social and demographic information collected. The Positive Subscale of Community Assessment of Psychic Experiences (CAPE) was used to measure PLEs, and the 7-item Generalized Anxiety Disorder Questionnaire (GAD-7) and the Edinburgh Postnatal Depression Scale (EPDS) were used to examine anxious and depressive symptoms, respectively. Logistic regression analyses were conducted to investigate the risk factors for pregnant women with PLEs. Results In our study, 37.2% of the pregnant women in this sample experienced at least one episode of PLEs, while 4.3% reported “often” having PLEs. More pregnant women experienced PLEs, delusional experiences, and hallucinatory experiences in the first two trimesters than in the third trimester. Factors associated with a higher risk for more frequent PLEs include: rural setting, unplanned pregnancy, parity 1, and EPDS scores. High positive correlations were shown between frequency scores among experiences of PLEs and GAD-7 scores, EPDS scores. Conclusion Episodes of PLEs are common in Chinese pregnant women; however, only a small proportion has persistent PLEs. It is vital to pay attention to women with psychosis risk in pregnancy.